The short-term impact of Ontario's generic pricing reforms. - Michael R Law; Alison Ystma; Steven G Morgan (PLoS ONE, 2011)
Canadians pay amongst the highest generic drug prices in the world. In July 2010, the province of Ontario enacted a policy that halved reimbursement for generic drugs from the public drug plan, and substantially lowered prices for private purchases. We quantified the impact of this policy on overall generic drug expenditures in the province, and projected the impact in other provinces had they mimicked this pricing change.We used quarterly prescription generic drug dispensing data from the IMS-Brogan CompuScript Audit. We used the price per unit in both the pre- and post-policy period and two economics price indexes to estimate the expenditure reduction in Ontario. Further, we used the post-policy Ontario prices to estimate the potential reduction in other provinces.We estimate that total expenditure on generic drugs in Ontario during the second half of 2010 was between $181 and $194 million below what would be expected if prices had remained at pre-policy level. Over half of the reduction in spending was due to savings on just 10 generic ingredients. If other provinces had matched Ontario's prices, their expenditures over during the latter half of 2010 would have been $445 million lower.We found that if Ontario's pricing scheme were adopted nationally, overall spending on generic drugs in Canada would drop at least $1.28 billion annually--a 5% decrease in total prescription drug expenditure. Other provinces should seriously consider both changes to their generic drug prices and the use of more competitive bulk purchasing policies.